AAPM TG 191: Clinical use of luminescent dosimeters: TLDs and OSLDs. Issue 2 (6th December 2019) - Kry, Stephen F.; Alvarez, Paola; Cygler, Joanna E.; DeWerd, Larry A.; Howell, Rebecca M.; Meeks, Sanford; O'Daniel, Jennifer; Reft, Chester; Sawakuchi, Gabriel; Yukihara, Eduardo G.; Mihailidis, Dimitris
Abstract : Thermoluminescent dosimeters (TLD) and optically stimulated luminescent dosimeters (OSLD) are practical, accurate, and precise tools for point dosimetry in medical physics applications. The charges of Task Group 191 were to detail the methodologies for practical and optimal luminescence dosimetry in a clinical setting. This includes: (a) to review the variety of TLD/OSLD materials available, including features and limitations of each; (b) to outline the optimal steps to achieve accurate and precise dosimetry with luminescent detectors and to evaluate the uncertainty induced when less rigorous procedures are used; (c) to develop consensus guidelines on the optimal use of luminescent dosimeters for clinical practice; and (d) to develop guidelines for special medically relevant uses of TLDs/OSLDs such as mixed photon/neutron field dosimetry, particle beam dosimetry, and skin dosimetry. While this report provides general guidelines for TLD and OSLD processes, the report provides specific details for TLD‐100 and nanoDot TM dosimeters because of their prevalence in clinical practice.